THE EFFECT OF STUDENT WORKSHEETS (LKPD) ON THE LEARNING OUTCOMES OF IPAS CLASS IV ELEMENTARY SCHOOL - Anisa Nurmala; Rahmiati (Universitas Majalengka, 2024)
This study aims to determine the influence of the use of LKPD (Student Worksheet) media on the learning outcomes of grade IV students of SDIT Setya Dharma Cileungsi Bogor in the subject of Natural and Social Sciences (IPAS). Using quantitative research methods, this study involved two groups: an experimental class that used LKPD and a control class that used conventional lecture methods. The research instrument has been tested for validity and reliability, with 30 out of 40 questions declared valid and have very high reliability. Data analysis includes normality tests, homogeneity, and hypothesis tests using independent sample t-tests. The results showed a significant difference between the experimental and control classes, with the average learning outcome of the experimental class (76.12) higher than that of the control class (62.94). The hypothesis test confirmed the significant influence of the use of LKPD on learning outcomes, as evidenced by the t-count value (5.618) > t-table (2.000) and the significance value of 0.000 < 0.05. In conclusion, the use of LKPD media has a significant positive influence on improving student learning outcomes in science and science subjects.